Health-related quality of life in premenopausal women with hormone-receptor-positive, HER2-negative advanced breast cancer treated with ribociclib plus endocrine therapy: results from a phase III randomized clinical trial (MONALEESA-7). (July 2020) - Harbeck, Nadia; Franke, Fabio; Villanueva-Vazquez, Rafael; Lu, Yen-Shen; Tripathy, Debu; Chow, Louis; Babu, Govind K; Im, Young-Hyuck; Chandiwana, David; Gaur, Anil; Lanoue, Brad; Rodriguez-Lorenc, Karen; et al.
Background: This analysis evaluated patient-reported outcomes (PROs) to assess health-related quality of life (HRQoL) in the phase III MONALEESA-7 trial, which previously demonstrated improvements in progression-free survival (PFS) and overall survival (OS) with ribociclib (cyclin-dependent kinase 4/6 inhibitor) + endocrine therapy (ET) compared with placebo + ET in pre- and perimenopausal patients with hormone-receptor-positive, HER2-negative (HR+/HER2−) advanced breast cancer (ABC). Methods: The European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life questionnaire C30 (QLQ-C30) and the EQ-5D-5L were used to evaluate HRQoL. Results: EORTC QLQ-C30 assessments were evaluable for 335 patients in the ribociclib arm and 337 patients in the placebo arm. Adherence rates at baseline and ⩾1 postbaseline time point were 90% and 83%, respectively. Patients treated with ribociclib + ET had a longer time to deterioration (TTD) ⩾ 10% in global HRQoL {hazard ratio (HR), 0.67 [95% confidence interval (CI), 0.52–0.86]}. TTD ⩾ 10% in global HRQoL was delayed in ribociclib-treated patients without versus with disease progression [HR, 0.31 (95% CI, 0.21–0.48)]. TTD ⩾ 10% in pain was longer with ribociclib + ET than with placebo + ET [HR, 0.65 (95% CI, 0.45–0.92)]. Patients who received a nonsteroidal aromatase inhibitor experienced similar benefits with ribociclib versus placebo in global HRQoL and pain. Conclusion: HRQoL was maintained longer in patients who received ribociclib + ET versus placebo + ET. These data, combined with previously reported improvements in PFS and OS, support a strong clinical benefit-to-risk ratio with ribociclib-based treatment in pre- and perimenopausal patients with HR+/HER2− ABC.